2019
DOI: 10.3389/fpsyg.2019.02094
|View full text |Cite
|
Sign up to set email alerts
|

Are Humans Prepared to Detect, Fear, and Avoid Snakes? The Mismatch Between Laboratory and Ecological Evidence

Abstract: Since Seligman (1971) statement that the vast majority of phobias are about objects essential to the survival of a species, a multitude of laboratory studies followed, supporting the finding that humans learn to fear and detect snakes (and other animals) faster than other stimuli. Most of these studies used schematic drawings, images, or pictures of snakes, and only a small amount of fieldwork in naturalistic environments was done. We address fear preparedness theories and automatic fast detection data from ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 118 publications
(148 reference statements)
0
27
0
Order By: Relevance
“…Even though the mortality rates attributed to serpents in the prehistoric times cannot be reliably quantified due to the snake highly efficient metabolism leaving no fossil records of their prey (Greene, 1983;Hsiang et al, 2015), some circumstantial evidence suggests that the emergence of snakes must have become a strong selection pressure in the mammalian evolution (Öhman and Mineka, 2003). As a consequence of the risk presented by snakes, human ancestors have developed a complex adaptive system of interconnected fear responses manifested on the psychological, behavioral, physiological, and neural level, which, according to some authors, has been embodied in a specific brain area, the so-called module of fear (Öhman and Mineka, 2001) localized in the amygdala (Öhman, 2005; Öhman et al, 2007; for a recent critical review of the modular theory, see Coelho et al, 2019). In fact, the modular theory has drawn upon the much earlier Seligman's (1971) concept of biological preparedness claiming that most of the clinical fears are triggered by stimuli threatening our survival in the evolutionary past.…”
Section: Snakes As Evolutionary Threat Triggering Fear and Disgustmentioning
confidence: 99%
“…Even though the mortality rates attributed to serpents in the prehistoric times cannot be reliably quantified due to the snake highly efficient metabolism leaving no fossil records of their prey (Greene, 1983;Hsiang et al, 2015), some circumstantial evidence suggests that the emergence of snakes must have become a strong selection pressure in the mammalian evolution (Öhman and Mineka, 2003). As a consequence of the risk presented by snakes, human ancestors have developed a complex adaptive system of interconnected fear responses manifested on the psychological, behavioral, physiological, and neural level, which, according to some authors, has been embodied in a specific brain area, the so-called module of fear (Öhman and Mineka, 2001) localized in the amygdala (Öhman, 2005; Öhman et al, 2007; for a recent critical review of the modular theory, see Coelho et al, 2019). In fact, the modular theory has drawn upon the much earlier Seligman's (1971) concept of biological preparedness claiming that most of the clinical fears are triggered by stimuli threatening our survival in the evolutionary past.…”
Section: Snakes As Evolutionary Threat Triggering Fear and Disgustmentioning
confidence: 99%
“…Alternatively, the stronger physiological response to venomous snakes found in our study might as well be explained by the need of activating energetic resources in dangerous situations, which is necessary for a fast and effective defense (fight-or-flight) response before a snakebite can be delivered, i.e., eliminate the source of threat or rather withdraw oneself from the snake's presence. However, in their latest review on presumed preparedness of fear of snakes, Coelho et al [51] argue, that most snakebites happen at very close vicinity and are extremely fast, so the victim usually has no chance to effectively respond.…”
Section: Psychophysiological Response To Viperid Snakes and How It MImentioning
confidence: 99%
“…They suggested a relevancebased explanation rather than an evolutionary-based explanation of threat detection. Interestingly, Coelho et al (2019) reported several challenges to evolutionary-based explanations of the snake detection theory and highlighted that the low-level features of the visual stimulus could have affected previous findings. Wolfe (2018) also suggested threat perception as a probable nonguiding attribute in visual search when the other basic features are controlled for.…”
Section: Discussionmentioning
confidence: 99%